How Idioms Are Recognized when Individuals Are "Thrown Off the Track", "Off the Rack" or "Off the Path": A Decision Time Experiment in Healthy Volunteers. (3rd July 2021) - Sandmann, Matthias; Weiss, Sabine; Mueller, Horst
ABSTRACT: Figurative elements in language have their own particularities, including words that deviate from their generally accepted definition to amplify our language or to paraphrase an issue. It is still unclear how individuals process idioms that are figurative or ambiguous, especially when they additionally become distracted by modified idioms that are similar in appearance. In our study, 47 healthy adults (mean age of 27.3 years, SD = 2.9) participated in a decision time experiment to determine how participants recognize well-formed, genuine German idioms alongside certain idiom modifications. All participants were initially exposed to a prime on a screen. Then, they had to detect the target idiom, which was presented alongside a systematically modified phonematic or semantic idiom. Using generalized linear mixed model regression analysis, we found that decisions related to a semantically modified idiom were made faster than decisions related to a phonematically modified idiom. The accuracy of correctly identifying an idiom was high (> 95%), regardless of the type of prime. Our findings indicate that complex idiomatic structures are more easily recognized when individuals are exposed to semantically modified idioms. Semantic information can be mapped onto the concept of the genuine idiom more quickly, which requires fewer mental resources.